PRAXIS OF CONSTRUCTIVIST LEARNING THEORY ON LEARNERS ACHIEVEMENT IN SECONDARY SCHOOL SCIENCE SUBJECTS IN KENYA - SHANI, OMINDE ELIUD; NGURE , DR. LUCY (IJRDO- Journal of Educational Research, 2019)
Constructivism is a philosophical stance on human knowledge that argues that human beings generate knowledge and meaning from an interaction between their experiences and their ideas (Alawiye, 2003). Odundo and Gunga (2013) observed that constructivism is a cognition theory that stimulates an individual learner to process stimuli from the environment and the resultant cognitive structures that allows the learner to build and produce adaptive behaviour.According to Mwanda (2016) the prominence of science education in the recent past has attracted great expectations from the teachers and general public who continuously advocate for increased performance in scientific inventions and the ability to apply and communicate scientific understandings. However, Poor performance of students in science subjects as a result of poor instructional strategies has been a major hindrance to the acquisition of scientific knowledge in Kenyan secondary schools.